Instructional Media for Fiqh of Funeral Rites: A Comparative Analysis in Indonesia and Thailand - Prawidya Lestari; Najmee Bindulem; Rizka Fatchurrohman (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2025)
This study provides a comparative analysis of learning media for the Fiqh of funeral rites at the secondary level, a topic that often creates pedagogical anxiety due to its sensitive and abstract nature. This qualitative study focuses on two institutions: Nurul Muttaqin Junior High School in Indonesia and Chariyathamsuksa Foundation School in Thailand, with data collected through interviews, observations, and document analysis. The results reveal two fundamentally different pedagogical models. Nurul Muttaqin implements a systematic, technology-integrated model, using videos and mannequins to reduce anxiety and ensure technical accuracy. Conversely, Chariyathamsuksa employs a communal, embodied learning model with students as proxies to demystify death and transmit values. This study demonstrates that the choice of media is not merely a technical decision but a profound reflection of institutional philosophy and socio-cultural context. The implications of this study challenge monolithic views of Islamic education and offer global insights into pedagogical adaptations for teaching sensitive religious materials.